MAGMA INTRUSION IN 'PROTO-CALDERA CALDERA' SYSTEMS: EXAMPLE FROM THE NISYROS VOLCANO - Zouzias, D.; St. Seymour, K. (Bulletin of the Geological Society of Greece, 2007)
The interdependence of volcanism and tectonism has been focused upon in the last decade as a result of previously accumulated evidence, as well as, due to the application of remote sensing techniques in both these fields. Volcanoes depend on tectonic features such as faults for their positioning and operation and on petrotectonic environment for the chemistry of their magmas. Faults provide the plumbing system for magma ascent and therefore volcano localisation and distribution in space greatly depends on the tectonic pattern of an area. On the other hand, volcanoes locally imprint their volcanotectonic features such as radial and ring faults which result from cycles of magma replenishment (inflation) and evacuation (deflation) of magmatic reservoirs (magma chambers). Under this light, the area in the easternmost extremity of the Aegean Arc is being reconsidered. Our main preliminary findings of ongoing research in the area, using field and remote sensing methods indicate localization of volcanic activity on Kos and on the Datca Peninsula of Asian Minor since Miocene due to the northbounding faults of the Datca Graben. Localisation of volcanic vents and calderas in the Kos-Nisyros area follows intersection of a major tectonic line of northnorthwesterly trending faults the 'Kos-Nisyros-Tilos Line' with N50°E, N30°E and N20°W trending faults. On the well-preserved volcano ofNisyros the architecture of the volcanic edifice has significantly been affected by 'trap-door' volcanotectonics of a major volcanic infrastructure in the area namely the Kos-Caldera